Lesbian, Gay, Biseksual, Transgender (LGBT) dalam Perspektif Fiqih - Nisa'atun nafisah; Tutik Hamidah (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2023)
In Muslim societies, LGBT issues are often a sensitive and complex debate, with some groups and scholars viewing them as a violation of religious norms, while others seek a more inclusive approach. The understanding of fiqh becomes the main foundation in explaining various aspects related to this controversial sexual identity and orientation. By adopting a qualitative research method, this study involves a literature study of various primary sources of Islamic fiqh. The study also provides an overview of the evolution of LGBT-related fiqh thinking and interpretation throughout Islamic history. The results show the diversity of scholars' approaches to LGBT issues, along with interpretations of scripture and principles of fiqh. The stipulations related to LGBT behavior in fiqh are explained differently in terms of the punishment stipulated based on the legal source. Thus, it can be concluded that the understanding of LGBT in through the dadil sourced from the Qur'an and hadith has formulated fiqh law.